Developing Practicum Module of Particle Dynamics Based on Scientific Methods to Improve Students' Science Process Skills - Irnin Agustina Dwi Astuti; Indra Yahdi Putra; Yoga Budi Bhakti (Scientiae Educatia: Jurnal Pendidikan Sains, 2018)
The existence of basic competence skills in the current national curriculum requires learners to have skilled expertise in the field of physics, which one of them is students’ science process skills. Students' science process skills become students’ guide in understanding physics concepts. The availability of resources and guidance in conducting practicum is very small, so teachers have difficulties when they want to conduct practicum in learning activities because of the lack of resources available. Therefore, we need a scientifically based practicum module to increase students’ science process skills. This development research using 4-D method (Define, Design, Develop, and Disseminate). In the development of this module, the researchers only come to the third stage of the four stages. Validation results from experts get an average score of 81% interpretation which means that the module is included in the criteria worthy of use in learning even with the notes of experts to revise some of the components present in this module so that this module complies with existing standards. The results of the analysis of student responses to the practicum module obtained a total average of 80% with the category is "strong." This shows almost all the students gave a positive response to the scientific-based practicum module. The development of scientific-based practicum modules can improve science process skills of the students, with the average score of students’ science process skills before using a scientific-based practicum module of 2.54 and the average score of students’ science process skills after using a scientific-based practicum module of 3.20.